Analysis of Production Area Planning at the CV. Victo Bandar Lampung Furniture Company - Triana, Rika; Defrizal, Defrizal (Lafadz Jaya Publisher, 2024)
The research carried out aims to determine efficient planning in terms of production area at the CV furniture company. Victo in Bandar Lampung. The approach used in this research involves quantitative descriptive analysis, with forecasting techniques using the Linear Trend method and Break Event Point analysis for data accuracy. The information obtained in this study comes from primary and secondary sources. Primary sources include direct interviews with company managers, while secondary sources are collected from company history. This data collection method includes interviews, direct observation, and review of related documents. The results of the research show that the production area for the coming year will be 533 units of cupboard products in 2023, 566 cupboard product units in 2024 and 600 cupboard product units in 2025, so that the CV. Victo furniture company in 2023-2025 will experience an increase of 6% of production area every year due to increasing trend demand. It is recommended that companies design their production area planning by applying the Linear Trend forecasting method and carrying out Break Event Point analysis to optimize their production processes and this research is expected to provide information for consideration for the company's progress. By knowing the correct production area planning calculations, it is hoped that the company's efficiency will increase so that it can reduce excessive production amounts and obtain even greater sales profits because needs have been well estimated.